2020
DOI: 10.1186/s12887-020-02022-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dietary factors associated with suspected pediatric nonalcoholic fatty liver disease and potential liver fibrosis: Korean National Health and Nutrition Examination Survey 2014-2017

Abstract: Background: The prevalence of nonalcoholic fatty liver disease (NAFLD) has increased as the obese pediatric population has increased. NAFLD causes progressive liver injury and the only effective treatment is lifestyle modifications. However, few studies have examined the dietary risk factors for pediatric NAFLD or liver fibrosis. Here, we evaluated the dietary factors associated with suspected NAFLD and potential liver fibrosis in Korean children. Methods: Data collected from 1674 children and adolescents aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Nonalcoholic fatty liver disease (NAFLD) is a complex disease that is closely related to genetic susceptibility and lifestyles. NAFLD has become the most common chronic liver disease worldwide in both adults and children ( 1 , 2 ). The global prevalence of NAFLD is currently estimated to be 32.4% in adults and 7.4% in children ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a complex disease that is closely related to genetic susceptibility and lifestyles. NAFLD has become the most common chronic liver disease worldwide in both adults and children ( 1 , 2 ). The global prevalence of NAFLD is currently estimated to be 32.4% in adults and 7.4% in children ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced steatosis was associated with lower serum aldosterone levels and downregulation of hepatic mineralocorticoid receptors; thus, decreased activation of hepatic mineralocorticoids may have resulted in beneficial downstream inhibition of lipogenesis [ 31 ]. However, many studies have reported the opposite: a high-salt diet has been linked to increased glucocorticoid production, insulin resistance, metabolic syndrome, and NAFLD development [ 32 , 33 , 34 ]. To draw a reasonable explanation for our results, we searched for food items that correlated with a high sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…The factors involved in driving the progression of NAFLD to fibrosis have been extensively evaluated. The 2 consistent risk factors for fibrosis development are metabolic syndrome and waist circumference [ 50 - 52 ]. Genetic variation is another source of wide study.…”
Section: Pediatric Liver Diseasesmentioning
confidence: 99%